Teori dan Konsep Literasi Budaya - Ridha Amalia; Andi Nurfadillah; Anri Anggraeni Iqbal; Abdul Muis; Muhammad Nawir (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
Cultural literacy is one of the essential competencies required in the twenty-first century to strengthen students' cultural identity, foster tolerance, and develop responsible citizenship in multicultural societies. This study aims to synthesize theories, concepts, principles, implementation strategies, and the educational significance of cultural literacy in elementary schools through a qualitative library research approach. Data were collected from books, scientific journals, policy documents, and other relevant academic sources, and analyzed using descriptive qualitative techniques involving data reduction, data display, and conclusion drawing. The review reveals that cultural literacy extends beyond understanding cultural diversity by serving as a foundation for character education, strengthening the Profile of Pancasila Students, preserving local wisdom, and enhancing citizenship literacy. The findings further indicate that effective implementation is achieved through the integration of cultural values into classroom instruction, the School Literacy Movement (GLS), School Literacy Teams (TLS), reading corners, local languages, traditional games, and collaboration among schools, families, communities, and government. Nevertheless, the review also identifies persistent challenges, including limited cultural learning resources, insufficient teacher competence, and inadequate stakeholder support. This study concludes that strengthening cultural literacy requires systematic collaboration and the integration of local cultural values into elementary education to develop culturally aware, tolerant, and globally competent learners.